Prediction of serum HIV-1 neutralization titers of VRC01 in HIV-uninfected Antibody Mediated Prevention (AMP) trial participants. Issue 1 (31st December 2022) - Huang, Yunda; Zhang, Lily; Eaton, Amanda; Mkhize, Nonhlanhla N.; Carpp, Lindsay N.; Rudnicki, Erika; DeCamp, Allan; Juraska, Michal; Randhawa, April; McDermott, Adrian; Ledgerwood, Julie; Andrew, Philip; et al.
ABSTRACT: VRC01 is being evaluated in the AMP efficacy trials, the first assessment of a passively administered broadly neutralizing monoclonal antibody (bnAb) for HIV-1 prevention. A key analysis will assess serum VRC01-mediated neutralization as a potential correlate of protection. To prepare for this analysis, we conducted a pilot study where we measured longitudinal VRC01 serum concentrations and serum VRC01-mediated neutralization in 47 and 31 HIV-1 uninfected AMP participants, respectively. We applied four different statistical approaches to predict serum VRC01-mediated neutralization titer against Env-pseudotyped viruses, including breakthrough viruses isolated from AMP placebo recipients who became HIV-1 infected during the trial, using VRC01 serum concentration and neutralization potency (IC50 or IC80) of the VRC01 clinical lot against the same virus. Approaches 3 and 4, which utilized pharmacokinetics/pharmacodynamics joint modeling of concentration and neutralization titer, generally performed the best or comparably to Approaches 1 and 2, which, respectively, utilized only measured and model-predicted concentration. For prediction of ID80 titers against breakthrough viruses, Approaches 1 and 2 rendered comparable performance to Approaches 3 and 4, and could be reasonable approaches to adopt in practice as they entail reduced assay cost and less complicated statistical analysis. Our results may be applied to future studies of other bnAbs and bnAb combinations to maximize resource efficiency in serum neutralization titer measurement.